Racial Differences in Clinical Outcomes for Metastatic Renal Cell Carcinoma Patients Treated With Immune-Checkpoint Blockade - Olsen, T. Anders; Martini, Dylan J.; Goyal, Subir; Liu, Yuan; Evans, Sean T.; Magod, Benjamin; Brown, Jacqueline T.; Yantorni, Lauren; Russler, Greta Anne; Caulfield, Sarah; Goldman, Jamie M.; Harris, Wayne B.; et al. (Frontiers in Oncology, 2021)
Background Immune-checkpoint-inhibitors (ICIs) have become the cornerstone of metastatic renal-cell-carcinoma (mRCC) therapy. However, data are limited regarding clinical outcomes by race. In this study, we compared the real-world outcomes between African American (AA) and Caucasian mRCC patients treated with ICIs. Methods We performed a retrospective study of 198 patients with mRCC who received ICI at the Emory Winship Cancer Institute from 2015-2020. Clinical outcomes were measured by overall survival (OS), progression-free survival (PFS), and overall response rate (ORR) defined as a complete or partial response maintained for at least 6 months per response evaluation criteria in solid tumors version 1.1. Univariate and multivariable analyses were carried out for OS and PFS by Cox proportional-hazard model and ORR by logistical-regression model. Descriptive statistics compared rates of immune-related adverse events (irAEs) and non-clear-cell-RCC (nccRCC) histology were assessed using Chi-square test. Results Our cohort was comprised of 38 AA and 160 Caucasian patients. Most were diagnosed with clear-cell-RCC (ccRCC) (78%) and more than half received (57%) PD-1/PD-L1 monotherapy. Most patients were intermediate or poor-risk groups (83%). Comparing to Caucasians, our AA cohort contained more females and nccRCC cases. Kaplan-Meier method showed AAs had no statistically different median OS (17 vs 25 months, p=0.368) and PFS (3.1 vs 4.4 months, p=0.068) relative to Caucasian patients. On multivariable analysis, AA patients had significantly shorter PFS (HR=1.52, 95% CI: 1.01-2.3, p=0.045), similar ORR (OR=1.04, 95% CI: 0.42-2.57, p=0.936) and comparable OS (HR=1.09, 95% CI: 0.61-1.95, p=0.778) relative to Caucasians. Conclusions Our real-world analysis of ICI-treated mRCC patients showed that AAs experienced shorter PFS but similar OS relative to Caucasians. This similarity in survival outcomes is reassuring for the use of ICI amongst real-world patient populations, however, the difference in treatment response is poorly represented in early outcomes data from clinical trials. Thus, the literature requires larger prospective studies to validate these findings.